EnvyDepth: An Interface for Recovering Local Natural Illumination from Environment Maps. (25th November 2013) - Banterle, Francesco; Callieri, Marco; Dellepiane, Matteo; Corsini, Massimiliano; Pellacini, Fabio; Scopigno, Roberto
Abstract: In this paper, we present EnvyDepth, an interface for recovering local illumination from a single HDR environment map. In EnvyDepth, the user quickly indicates strokes to mark regions of the environment map that should be grouped together in a single geometric primitive. From these annotated strokes, EnvyDepth uses edit propagation to create a detailed collection of virtual point lights that reproduce both the local and the distant lighting effects in the original scene. When compared to the sole use of the distant illumination, the added spatial information better reproduces a variety of local effects such as shadows, highlights and caustics. Without the effort needed to create precise scene reconstructions, EnvyDepth annotations take only tens of seconds to produce a plausible lighting without visible artifacts. This is easy to obtain even in the case of complex scenes, both indoors and outdoors. The generated lighting environments work well in a production pipeline since they are efficient to use and able to produce accurate renderings.